2015 International Conference on Computer, Information and Telecommunication Systems (CITS) 2015
DOI: 10.1109/cits.2015.7297764
|View full text |Cite
|
Sign up to set email alerts
|

Sum-rate maximizing cell association via dual-connectivity

Abstract: This paper proposes a dual-connectivity (DC) profile allocation algorithm, in which a central macro base station (MBS) is underlaid with randomly scattered small base stations (SBSs), operating on different carrier frequencies. We introduce two dual-connectivity profiles and the differences among them. We utilize the characteristics of dual-connectivity profiles and their applying scenarios to reduce feasible combination set to consider. Algorithm analysis and numerical results verify that our proposed algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Proof. We first note that the problem in (21) is indeed equivalent to (16) by the macro and resourceγû b ,b by pico TP b. Then, for that user we can bound the rate as…”
Section: A Optimal Allocation Fractions Of (1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. We first note that the problem in (21) is indeed equivalent to (16) by the macro and resourceγû b ,b by pico TP b. Then, for that user we can bound the rate as…”
Section: A Optimal Allocation Fractions Of (1)mentioning
confidence: 99%
“…On the other hand, [14] considers resource partitioning at only the macro node in a DC enabled downlink to optimize the PF utility. [16] proposes an efficient sub-optimal algorithm for the problem of determining the sum rate maximizing user association under the restrictions that for each user only the low-power node yielding the highest SINR can be chosen and each node employs round robin scheduling. [17] evaluates algorithms that aim to maximize the number of satisfied users, .i.e., aim to satisfy minimum rate requirements for as many users as possible via single-TP association as well as DC.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], the authors propose a downlink traffic scheduling scheme for maximization of the network throughput. [8], [9] deal with maximizing the data rate of DC users in LTE and multiple-Radio Access Technology (RAT) scenario, respectively. The works [7], [9], [10] consider throughput as the system metric of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Dual connectivity allows users to be simultaneously served by an MBS and a pico base station (PBS), which are operating at nonoverlapping frequency carriers and are interconnected with X2-based backhaul links. It has been demonstrated that dual connectivity can significantly increase the user throughput [2][3][4] and at the same time improve the robustness against mobility [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous works [3,4,7,8] address the traffic splitting optimization with dual connectivity without jointly considering the user-PBS association optimization and backhaul limitations. In this work, we focus on the optimization of traffic splitting and user-PBS association in the uplink by taking into account the backhaul capacity constraints of the single-antenna PBSs, where the MBS is equipped with a large number of antennas.…”
Section: Introductionmentioning
confidence: 99%